2014
DOI: 10.1161/hypertensionaha.114.03533
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Blood Pressure and Arterial Stiffness in Chronic Kidney Disease

Abstract: day) becomes more apparent. Importantly, loss of nocturnal dipping is associated with CKD progression.11 However, these studies did not explore interventions to restore BP dipping.Arterial stiffness also contributes significantly to the CVD risk in CKD. 12 Although some studies have examined daytime variations in arterial stiffness, none has included patients with CKD. 13,14 Furthermore, no study has as yet addressed ambulatory arterial stiffness and its 24-hour variation. Thus, there is a need for newer treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 58 publications
4
34
0
1
Order By: Relevance
“…Left ventricular hypertrophy is an important complication of chronic kidney disease, and there was a significant positive correlation between elevated plasma endothelin-1 and LVMI. As seen in Table 4, after adjusting the regression equation by systolic blood pressure, it can prove that ET-1 induced ventricular hypertrophy non-dependent of blood pressure [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular hypertrophy is an important complication of chronic kidney disease, and there was a significant positive correlation between elevated plasma endothelin-1 and LVMI. As seen in Table 4, after adjusting the regression equation by systolic blood pressure, it can prove that ET-1 induced ventricular hypertrophy non-dependent of blood pressure [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and hypertension are the leading causes of CKD, but interestingly, the loss of normal BP rhythms in individuals with CKD has been well documented and may be a contributing factor for CKD progression [124,161,162]. The association and prevalence of non-dipping BP with a decline in renal function has also been previously reported [163165], suggesting an impairment of the circadian clock mechanism in patients with the disease.…”
Section: Pathologies Associated With Impaired Circadian Rhythmsmentioning
confidence: 98%
“…In healthy individuals, there is a diurnal difference in the levels of plasma ET-1, with lower levels observed at night [124], but this is less evident in rats [76] (Fig. 5).…”
Section: Integration Of Circadian Control Throughout the Nephronmentioning
confidence: 99%
“…These additional effects may, in theory, confer improved cardiovascular and renal protection. 90,116 With regard to the safety data from this study, in contrast to the effects of other ERAs in diabetic nephropathy, it is worth noting that there was no evidence of fluid retention within this cohort. Sitaxentan has been shown to have no functional effect on ET B in vivo in human beings 117 and these observations would be consistent with a role for ET B in fluid accumulation.…”
Section: Clinical Studiesmentioning
confidence: 76%
“…In patients with CKD, however, ET A activity appears increased, with a preferential effect on the efferent arteriole, raising the possibility that ET-1 promotes hyperfiltration in CKD. The vasoconstrictor effect of BQ788 in both health and disease suggests that ET B plays an important role in maintaining basal systemic 90,115,116 Sitaxentan therapy also improved markers of arterial stiffness, improved nocturnal BP dip, and reduced plasma asymmetric dimethylarginine (ADMA) and uric acid and renal vascular tone, and indicates that its blockade in CKD may have negative consequences on both systemic BP and renal blood flow. 111 A further acute study, using BQ123, in 22 patients with nondiabetic proteinuric CKD found that BQ123 caused significant reductions in BP and arterial stiffness and increased renal blood flow while causing a decrease in proteinuria of approximately 30%.…”
Section: Clinical Studiesmentioning
confidence: 99%